TRAJEKTORI PEMEROLEHAN FONOLOGI DAN INTERAKSI SINTAKSIS PADA ANAK USIA 3 TAHUN PENUTUR BAHASA INDONESIA: ANALISIS BERBASIS FUNCTIONAL GRAMMAR - Indah Maulina, Alfira; Sepri Yusnalda, Aisya; Fauzia, Annisa; Vonita, Mediza; Rahmadia, Meisya; Rahma Dewi, Mutia; Delima, Nanda; Hasnul Ulya, Ridha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the dynamics of phonological acquisition and its interaction with syntactic development in three-year-old children who are native speakers of Indonesian. The study applies a mixed-method design through intensive observation over one and a half months. Spontaneous speech data were collected using the 'simak libat cakap' technique, strictly validated through linguistic expert triangulation, and processed quantitatively by calculating the frequency of phonological processes and Mean Length of Utterance (MLU). Qualitative analysis was conducted using the Functional Grammar framework and contemporary language acquisition theory. The results reveal the dominance of deletion processes (55.3%, especially apheresis), substitution (21.3%), assimilation, addition, distortion, and onomatopoeia. An MLU value of 1.8 morphemes confirms the developmental transition from simple nominal structures to multi-component grammatical relations. The conclusion asserts that phonological modification functions as an adaptive strategy adaptive and aligned with the expansion of syntactic and pragmatic competence. Theoretically, the findings reinforce usage-based approaches and dynamic systems models in developmental psycholinguistics. Practically, the implications provide a precise clinical diagnostic framework as well as a responsive pedagogical foundation for early childhood language stimulation through recasting techniques and natural input modeling.